ANALISIS PERSEPSI MUZAKI TERHADAP PREFERENSI DAN KEPUTUSAN MEMILIH LEMBAGA AMIL ZAKAT (STUDI KASUS DI KOTA MEDAN DAN SEKITARNYA) - Darma, Satria; Siregar, Saparuddin; Rokan, Mustafa Kamal (IAIN Langsa, 2017)
The objective of this research is; firstly to analyze the impact of the perceptions, that the perception of service, promotions and location of the Muzaki?s preferences, then to analyze the impact of the preferences towards Muzaki?s decision, and finally to analyze the impact of the perceptions of service, promotions, location and preferences of Muzaki?s decision in choosing LAZ. This research is a quantitative research using path analysis method through LISREL 8.80 assisted by MSI (Method of Succesive Interval) and SPSS 16.0 application tool to test the feasibility of the data. The results showed that perception of service very influential to preference compared with promotion and location. And Preference has a significant influence on decisions rather than perceptions of service, promotion and location. This study recommends Amil Zakat Institute to be able to improve the service because it is a matter of great concern and felt directly by muzaki and become preference for muzaki in determining its decision in choosing Amil Zakat Institution.